Functionalization of basalt fibers with ZnO nanostructures by electroless deposition for improving the interfacial adhesion of basalt fibers/epoxy resin composites. (October 2021) - Preda, Nicoleta; Costas, Andreea; Lilli, Matteo; Sbardella, Francesca; Scheffler, Christina; Tirillò, Jacopo; Sarasini, Fabrizio
Highlights: ZnO-coated basalt fibers were prepared by a low cost and scalable electroless deposition. Basalt fibers were uniformly coated with ZnO prisms shaped crystallites. Mechanical properties of modified basalt fibers were preserved. ZnO prisms were beneficial to enhance interfacial properties with epoxy matrix. Abstract: Basalt fibers were functionalized by ZnO electroless deposition for obtaining a nanostructured interphase for enhancing the interfacial strength with an epoxy resin matrix. The structural, morphological and wetting properties of the pristine basalt fabrics and ZnO-coated basalt fabrics were evaluated. The fabrics were uniformly coated with ZnO nanostructures featuring a wurtzite structure and a twin hexagonal prism morphology. The contact angle measurements revealed that ZnO prisms transformed the hydrophilic basalt fabric into a hydrophobic one (~130°). ZnOs were also grown on the basalt fibers as yarns to evaluate their interfacial adhesion by single fiber pull-out tests. The results emphasize significant improvement in the apparent interfacial shear strength (~42%) with limited degradation of the pristine basalt fiber tensile strength (a reduction of ~ 17%). Therefore, ZnO electroless deposition can be regarded as an effective route to improve the mechanical performance of basalt/epoxy composites expanding their potential range of applications as structural materials.